EXPERIMENTAL STUDY OF ULTRASONIC RAYLEIGH WAVE SCATTERING AT A THIN ANISOTROPIC SLAB - Its E.; Lee J.; Anisimov A. (My University, 2000)
In this article we report the results of 3D ultrasonic experiments on Rayleigh wave scattering by a narrow vertical anisotropic slab. The experimental model was built from two rectangular isotropic blocks with a narrow, vertical, anisotropic slab embedded between them. To provide a welded contact between the blocks and the slab, an epoxy glue was applied. The slab was made of woodfiber with the fiber oriented horizontally along the surfaces of the slab. Scattered waves were recorded in the far-field zone, in the vicinity of the slab and inside the slab. The results of the experiments for the far-field zone are compared with the results of mathematical modeling using the Green's function technique for thin anisotropic layers. Welded and nonwelded boundary conditions were used in the mathematical model to take into account the epoxy glue layer. The experimental and theoretical results are largely consistent for the welded boundary condition model. Significant variations of Rayleigh wave amplitudes, which cannot be explained in the framework of the Green's function method, were observed in a wavelength-scale zone near the slab.